SOSIALISASI DESA/KELURAHAN RAMAH PEREMPUAN DAN PEDULI ANAK DI LINGKUNGAN TERITIH KOTA SERANG - Yeni Widyastuti; Arenawati Arenawati (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Teritih Village has problems with low educational participation of women who live in villages, exploitation of women, many female workers as the backbone of the family while their husbands are unemployed, so that the role of breadwinner that should be done by the husband is shifted to the wife, the divorce rate is due to early marriage, in some cases the divorced wife is left alone by her husband without being given a living for her children and there have been several cases of violence against women and children due to economic factors. The purpose of this community service activity is to provide education and awareness regarding the implementation and benefits of Environmentally Friendly Villages and reducing cases of violence against women and children. The community service method used is counseling. The results of the study explain that this RPPA has become a need for the village itself, there is a need for a decent and safe village environment to live in, especially for women and children. That is why women and children must be fully involved because they are the ones who understand the issues around them and know the most appropriate solutions for their welfare, ensuring that the village empowers women in gender-based entrepreneurship accompanied by the process of building critical awareness of women, the village creates an environment that supports the process of child growth and development and encourages the role and responsibility of both parents and families in quality child care, the village makes special efforts to stop violence against women and children, the village makes special efforts to stop child marriage and most importantly, the community understands the forms of violence, understands where to report if they see, hear and become victims in cases of violence, the outreach and case assistance system runs well.Keywords: Abuse; Children; Public Awareness; Women;